Relationship between Homeostatic Model Assessment for Insulin Resistance and Waist Hip Ratio with Cognitive Function in Type 2 Diabetes Mellitus - Fitri, Fasihah Irfani; Novita, Oriza; Hutagalung, Haflin Soraya (CoinReads Media Prima, 2023)
Introduction: Cognitive impairment is a common complication of Type 2 Diabetes Mellitus (T2DM) in which the underlying mechanism are insulin resistance and associated central obesity. Homeostatic model assessment of insulin resistance (HOMA-IR) and waist-hip ratio (WHR) have been used as markers for insulin resistance and central obesity, respectively, but their direct association with cognition remains unclear. This study was conducted to determine the relationship between HOMA-IR and WHR with cognitive function in T2DM patients. Method: This was a correlative analytic study with a cross sectional design involving T2DM pateints. The HOMA-IR was assessed based on blood laboratory results, the WHR was measured by dividing circumference of the waist by the circumference of the hips and cognitive function was assessed using the Montreal Cognitive Assessment Indonesian Version (MoCA-INA). Results: : There were 56 patients included in the study. There was no significant relationship between HOMA-IR and cognitive function in T2DM patients (p=0.276; r=0.148). There was also no significant relationship between WHR and cognitive function (p = 0.499; r = 0.092). Conclusion: The HOMA-IR and WHR were not correlated with cognitive function in T2DM.